Factors affecting the subjective financial well-being of emerging adults in Malaysia - Loh, Emily Li Yeng; Ean, Joanne Zi En; Kim, Hui May; Loo, Min Wen; Wong, Shin Yi (2021)
Emerging adults in Malaysia are facing financial stress which can lead to a low subjective financial well-being. The subjective financial well-being is very personal and difference for each individual. The subjective financial well-being is usually lower for emerging adulthood because they are experiencing a change of life stage from dependent to independent. Many uncertainties make them worry about their financial conditions. The purpose of this research is to investigate the factors that affect subjective financial well-being of emerging adults in Malaysia. The independent variable including financial stress, financial attitude, internal locus of control and financial knowledge. In order to conduct informative research during this Covid-19 pandemic, questionnaire is constructed online through Google Form and distributed electronically to 364 emerging adults in Klang Valley. The data are then collected and reclassify in order for the analysis can be done. The analysis that done by using SPSS software including the consistency, significance and relationship between variables. The results from SPSS show financial stress, financial attitude and internal locus of control have a significant relationship with subjective financial well-being. However, financial knowledge shows an insignificant relationship on subjective financial well-being. The research findings contribute to academia, government and society.